1987
DOI: 10.1037/0022-0167.34.2.228.b
|View full text |Cite
|
Sign up to set email alerts
|

Counselor's reputation: An important precounseling variable for adolescents.

Abstract: The purpose of this research was to determine the precounseling effects of reputational cues on high school students 1 preferences for counselors and perceptions of the counselor's credibility and interpersonal attractiveness. In two separate but similar experiments, 485 students each saw one of seven experimental conditions presented on videotape. On three videotapes, high school students delivered positive, neutral, or negative reputational cues about a male or a female counselor. Three additional videotapes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…At least 27 studies examined the effect of objective evidence of training, various counselor behaviors, prestigious cues, and personal characteristics on perceived counselor expertness. Briefly, the research on the effect of objective evidence of training and of prestigious cues found results consistent with the research in the last reviews (except Strohmer & Biggs, 1983); objective evidence of training and prestigious cues did consistently affect perceptions of counselor expertness (Angle & Goodyear, 1984;Bernstein & Figioli, 1983;Littrell, Caffrey, & Hopper, 1987;McCarthy, 1982;Paradise, Conway, & Zweig, 1986).…”
Section: Stage 1: Establishing a Base For Influence Counselor Variabl...supporting
confidence: 76%
“…At least 27 studies examined the effect of objective evidence of training, various counselor behaviors, prestigious cues, and personal characteristics on perceived counselor expertness. Briefly, the research on the effect of objective evidence of training and of prestigious cues found results consistent with the research in the last reviews (except Strohmer & Biggs, 1983); objective evidence of training and prestigious cues did consistently affect perceptions of counselor expertness (Angle & Goodyear, 1984;Bernstein & Figioli, 1983;Littrell, Caffrey, & Hopper, 1987;McCarthy, 1982;Paradise, Conway, & Zweig, 1986).…”
Section: Stage 1: Establishing a Base For Influence Counselor Variabl...supporting
confidence: 76%
“…We were able to find four analogue adolescent treatment credibility studies that were from the 1980's (Atkinson & Schwartz, 1984;Bernstein & Figioli, 1983;Lee, Hallberg, Jones, & Haase, 1980;Littrell, Caffrey, & Hopper, 1987) and one actual treatment credibility study (Stein et al, 2001). Obviously, more research is needed in the youth mental health treatment literature to see if this is also an important common process factor in youth-therapist interactions.…”
Section: Therapist Credibility/ Persuasivenessmentioning
confidence: 99%
“…Consequently, much of the research on social influence has focused on examining specific counseling behaviors that influence clients' perceptions of counselors, such as nonverbal behaviors (Robbins & Haase, 1985), interpretation style (Milne & Dowd, 1983), self-disclosure (Dowd & Boroto, 1982), reputation (Littrell, Caffrey, & Hopper, 1987), attractiveness (Vargas & Borkowski, 1983), profanity (Paradise, Cohl, & Zweig, 1980), attire (Roll & Roll, 1984), touch (Suiter & Goodyear, 1985), psychological jargon (Atkinson & Carskaddon, 1975), and status (McCarthy, 1982). Another specific counselor behavior, which to date has not been examined in the social influence literature, is note-taking behavior.…”
mentioning
confidence: 99%